Sialomucin complex at the rat ocular surface: a new model for ocular surface protection. - Price-Schiavi, S A (1998)
The ocular surface, which is among the most accessible and vulnerable tissues in mammals, is protected by a complex tear film composed of lipid, aqueous and mucin layers. In spite of its importance, the molecular nature of the mucin contribution remains uncertain. Since membrane mucins have been implicated in the protection of other epithelia, we have analysed rat corneal and conjunctival tissues for sialomucin complex (SMC), a membrane mucin found at the apical epithelial cell surfaces in the airway and uterus. Using Northern and Western blot analyses, SMC expression was found in both ocular tissues, being particularly abundant in the cornea. In contrast with the other known membrane mucin, MUC1, SMC was localized more heavily towards the apical surface of the epithelial cells. SMC in ocular surface epithelia was produced in both soluble and membrane forms, the latter being found predominantly in the most superficial cells and at apical surfaces. The soluble form was found loosely adsorbed to apical cell surfaces, particularly of the cornea, as indicated by a mild rinsing protocol. Finally, the tear fluid contained substantial amounts of SMC. From these results, we propose a new model for tear mucin components in which SMC is expressed at the apical ocular surface in both membrane-bound and adsorbed soluble forms to provide a direct protective barrier. SMC secreted into the tear fluid may also participate in maintaining the stability of the preocular tear film by acting with other secreted mucins to determine the physical properties and protective behaviour of the tear film.